MEDIA VISUALISASI PENDIDIKAN SEKS PRANIKAH UNTUK PENYULUHAN SEBAYA - Yulia Fajrin; Ellysa Tjandra; Tyrza Adelia (CALYPTRA, 2018)
Sex education or information provision about sexual problems to adolescents is an important thing, where the goal is to maintain and respect their bodies. Sex education itself is widely provided by institutions that provide health services for adolescents, one of them is Sebaya PKBI Jawa Timur who do counseling to adolescents in Surabaya. They give informations to the audience using slide power point and metaplan as their media, but the delivery of the information is less interactive and informative. This shortcomings makes it difficult for an audience in the 10-19 years age group to understand the information presented. After knowing the problem, collecting theoretical basis about Infographic, Sexual Reproduction, Sexually Transmitted Infections and HIV / AIDS, doing analysis on similar media and system requirement analysis, then Media Visualization of Sex Education for SeBAYA’s Counseling will be created. Character design stage until page design will be implemented in this Final Project. Media Visualization of Sex Education for SeBAYA’s Counseling has some menu such as Home, Select Materials, About SeBAYA, Credit. Select Materials Menu containing infographic videos about Puberty, Gender, Sexually Transmitted Diseases and Teen Rights. About SeBAYA menu contains information about SeBAYA Organization. Credit menu contains information about the author, lecturers, and audio sources used in the program. This application is implemented using Adobe Illustrator CS6, Adobe Animate CC, Adobe After Effect CS6, and Garage Band. After the implementation phase, the trial and evaluation stage are performed. The results of the trial states are Media Visualization of Sex Education for SeBAYA’s Counseling is an interesting media and can help in counseling about Sex Education.